Revisiting the implementation of active learning pedagogy in EFL classrooms - Merina Devira (Studies in English Language and Education, 2020)
The present study investigated the current development of active learning pedagogy implementation, focusing on the English subject, at high school classrooms in Langsa, Aceh, Indonesia. It focused on English teachers’ pedagogical practices undertaken at the classrooms during the lessons and the factors impeding the construction of active learning methodology. A qualitative method was used, which employed the instruments of classroom observations, interviews, and lesson plan reviews. It was conducted in four lessons at three different high schools located in eastern Aceh, Langsa. The participants of this study were four English teachers and eleventh grade students who were actively involved in the observed English lessons. The findings showed that the dominant teachers’ role and students’ engagement in the class teaching-learning practices were not yet incorporated as active learning principles. Then, there was a lack of teachers’ understanding on the concept of active learning pedagogy, less provided trainings on active learning methodology, no provision of teaching-learning media at classrooms, and individual students were considered as influential factors in implementing an active learning pedagogy in these classrooms. Hence, future researchers are recommended to conduct an adaptation or re-evaluation to the active learning methodology that has been used all these times in order to be more practical and appropriate with Indonesian classroom contexts.